ISLAMIC DA'WAH IN SOCIAL MEDIA IN AL-HIKMAH SMA STUDENTS SURABAYA (CASE STUDY OF DAKWAH COMMUNICATION IN SOCIAL MEDIA IN AL-HIKMAH SMA STUDENTS SURABAYA) - mila astriana (Wasilatuna: Jurnal Komunikasi dan Penyiaran Islam, 2022)
The existence of the internet greatly facilitates humans in finding information, establishing communication and providing solutions in various aspects of human life. It is also supported by the presence of social media in the midst of the community who take part in providing information about religion and da'wah in cyberspace. Da'wah literacy by utilizing social media has become a new da'wah method that is in vogue in recent years. In fact, you could say that social media is one of the solutions for the right da'wah method during the Covid-19 pandemic. Religious activities through social media are also widely carried out by Muslim students in Surabaya. They study Islam by browsing information from the internet and using social media. Students are free to choose religious information, for example listening to preaching tausiyah material from the ustadz they idolize. There are indications that they use social media as their alternative in studying Islam. This study aims to prove the existence of the phenomenon of da'wah islam in social media at Al-Hikmah High School Surabaya students. The analytical approach that the author uses in this research is Alfred Schutz's tradition of phenomenological thought related to Islamic da'wah activities as a social phenomenon. In this study, the authors used a qualitative method.